Radiofrekvencní katetrová ablace paroxyzmální fibrilace síní konvencní metodou, bezprostrední a dlouhodobé výsledky - Lábrová, R; Fiala, M; Toman, O; Spinar, J (Vnitrni lekarstvi, 2008)
INTRODUCTION: Atrial fibrillation is the most frequent cardiac arrhythmia. Epidemiological studies show sharp increase of incidence and prevalence of atrial fibrillation all over the world. Atrial fibrillation is becoming to be a serious problem, not only clinical, but even social and economical. Aim of the paper was to evaluate immediate and long-term results of radiofrequency catheter ablation of paroxysmal atrial fibrillation at Dpt. of Internal Medicine-Cardiology, University Hospital Brno. METHODS: The patients were indicated for ablation, when the anti-arrhythmic therapy was ineffective. End-point of the ablation was disconnection of myocardial sleeves between left atrium and pulmonary veins and complete electrical isolation of pulmonary veins. GROUP OF THE PATIENTS, RESULTS: There were 67 catheter ablations of paroxysmal atrial fibrillation performed within the years 9/2004 to 12/2006 at our department, out of the whole amount of 1,285 ablations of supraventricular tachyarrhythmias from 1995 to 2006. There were 27 women (40%) and 40 men (60%) in our group of patients, with the mean age 56.9 +/- 9.5 years. The average ejection fraction of left ventricle was 62 +/- 5%, left atrial dimension 42.8 +/- 6 mm. The mean follow-up period was 16.9 +/- 10.9 months. The patients were treated before and after the ablation by 1 anti-arrhythmic drug in 44.8 vs 50%, by 2 drugs in 40.3 vs 14.9% and by 3 drugs in 10.4 vs 9%, respectively. The percentage of patients without any anti-arrhythmic drug increased after successful ablation from 2.9 to 25.4%, the percentage of patients using amiodarone decreased from 29.8 to 16.4%, propafenon from 29.8 to 16.4% and sotalol from 26.8 to 10.4% respectively. The median of RF application duration was 43.8 min, fluoroscopy time 43.8 min and procedure duration 240 min. The success rates were 87.5% in year 2004, 77.4% in 2005 and 79.2% in 2006. CONCLUSION: Catheter ablation of paroxysmal atrial fibrillation has become a routine curative method in symptomatic patients without major structural heart disease, with ineffective anti-arrhythmic treatment. Ablation was associated with significant reduction of anti-arrhythmic and anticoagulation therapy.
Keywords: Female; lidé středního věku; Echocardiography; mužské pohlaví; Atrial Fibrillation; Humans; dospělí; tepový objem; lidé; Catheter Ablation; Middle Aged; fibrilace síní; senioři; Stroke Volume; echokardiografie; Treatment Outcome; ženské pohlaví; katetrizační ablace; Aged; Adult; Male; výsledek terapie